Tropicamide Versus Cyclopentolate for Cycloplegic Refraction in Pediatric Patients With Brown Irides: A Randomized Clinical Trial - Wejdan Al-Thawabieh (17632236) (2023)
Purpose To compare the final cycloplegic refraction of tropicamide 1% and cyclopentolate 1% in children 3-16 years of age with brown irides. Design Randomized, controlled, multicenter prospective clinical trial. Methods Included patients were randomized to either cyclopentolate 1% or tropicamide 1% in the first visit with autorefraction measurements. Each subject underwent a second cycloplegic refraction using the other agent on a separate visit with a minimum of 1-week interval and a maximum of 12 weeks. We measured the change in SE (ΔSE) for each eye by deducting the SE before cycloplegia from the SE after cycloplegia. Results A total of 185 eyes from 94 children aged 3-16 years (average= 8.79 ±3.11 years) were included. The average SE of both eyes before cycloplegia was –0.082 ± 4.8 diopters. The SE after instillation of cyclopentolate and tropicamide in both eyes was 1.07±5.2 and 0.96±5.1, respectively (P value < .001). The average ΔSE after cycloplegia was 1.15±1.2 for cyclopentolate and 1.04±1.2 for tropicamide (P value < .001). The difference between ΔSE of cyclopentolate and tropicamide was found statistically significant at 0.11±1.2 (P < .001), although clinically insignificant. The ΔSE between the 2 drops before and after cycloplegia in both eyes for all refractive error groups was clinically insignificant. The greatest effect of cyclopentolate and tropicamide was in hyperopic eyes with ΔSE of 1.54±1.4 and 1.39±1.4, respectively. Conclusions Tropicamide might be an effective and safe replacement for cyclopentolate in the refracting nonstrabismic pediatric population 3-16 years of age regardless of their refractive error status. Other Information Published in: American Journal of Ophthalmology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.ajo.2023.09.022